Opioid use disorder: current trends and potential treatments - Lee, Yu Kyung; Gold, Mark S.; Blum, Kenneth; Thanos, Panayotis K.; Hanna, Colin; Fuehrlein, Brian S. (Frontiers in Public Health, 2024)
Opioid use disorder (OUD) is a major public health threat, contributing to morbidity and mortality from addiction, overdose, and related medical conditions. Despite our increasing knowledge about the pathophysiology and existing medical treatments of OUD, it has remained a relapsing and remitting disorder for decades, with rising deaths from overdoses, rather than declining. The COVID-19 pandemic has accelerated the increase in overall substance use and interrupted access to treatment. If increased naloxone access, more buprenorphine prescribers, greater access to treatment, enhanced reimbursement, less stigma and various harm reduction strategies were effective for OUD, overdose deaths would not be at an all-time high. Different prevention and treatment approaches are needed to reverse the concerning trend in OUD. This article will review the recent trends and limitations on existing medications for OUD and briefly review novel approaches to treatment that have the potential to be more durable and effective than existing medications. The focus will be on promising interventional treatments, psychedelics, neuroimmune, neutraceutical, and electromagnetic therapies. At different phases of investigation and FDA approval, these novel approaches have the potential to not just reduce overdoses and deaths, but attenuate OUD, as well as address existing comorbid disorders.